2011
DOI: 10.1002/jcp.22671
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen in cycling rats alters gene expression in the temporomandibular joint, trigeminal ganglia and trigeminal subnucleus caudalis/upper cervical cord junction

Abstract: Females report temporomandibular joint (TMJ) pain more than men and studies suggest estrogen modulates this pain response. Our goal in this study was to determine genes that are modulated by physiological levels of 17β-estradiol that could have a role in TMJ pain. To complete this goal, saline or complete Freund's adjuvant was injected in the TMJ when plasma 17β-estradiol was low or when it was at a high proestrus level. TMJ, trigeminal ganglion and trigeminal subnucleus caudalis/upper cervical cord junction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 70 publications
3
43
0
Order By: Relevance
“…Interestingly, in terms of the severity for TMD, sharper symptoms of TMDs were exhibited in females than in males [25,26]. The exact reasons have not yet been determined; however, given the striking predominance of affected women, previous studies proposed that the results could be partially attributed to hormonal influence, and a rise in estrogen levels may be an important risk factor for the pathogenesis of TMD [25,[27][28][29]. It should be emphasized that TMDs are complex multifactorial disorders.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, in terms of the severity for TMD, sharper symptoms of TMDs were exhibited in females than in males [25,26]. The exact reasons have not yet been determined; however, given the striking predominance of affected women, previous studies proposed that the results could be partially attributed to hormonal influence, and a rise in estrogen levels may be an important risk factor for the pathogenesis of TMD [25,[27][28][29]. It should be emphasized that TMDs are complex multifactorial disorders.…”
Section: Discussionmentioning
confidence: 86%
“…Prolonged exposure to estradiol in neuronal cultures from DRGs of female rats inhibits activation of the ion channel TRPV1, which is central to nociceptive transmission in the DRG (Xu et al, 2008) and cultured trigeminal ganglion cells from ovariectomized rats exhibit increased sensitivity to capsaicin (Diogenes et al, 2006). The expression of various painrelated peptides in the mouse trigeminal ganglion also varies with the estrous cycle (Puri et al, 2011;Puri et al, 2005). Estradiol modulates the expression of P2X3 receptors, known to be involved in peripheral pain signaling, in the trigeminal and dorsal root ganglia thereby affecting nociceptive transmission in the ovariectomized rat Yu et al, 2011).…”
Section: Additional Pain Modulatory Effectsmentioning
confidence: 99%
“…Moreover, different concentrations of estradiol during the menstral cycle affect the orofacial pain response (Yu et al). To determine how estradiol could potentially alter orofacial sensitivity, gene expression in the TMJ, trigeminal ganglia (TG) and trigeminal subnucleus caudalis/upper cervical cord region (Vc/C 1-2 ) was analyzed with gene arrays after treating rats with physiological doses of 17 β-estradiol (Puri et al, 2011). A subunit of the GABA A receptor, Gabrα6, was affected by 17 β-estradiol in the TG and Vc-C 1 (Puri et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To determine how estradiol could potentially alter orofacial sensitivity, gene expression in the TMJ, trigeminal ganglia (TG) and trigeminal subnucleus caudalis/upper cervical cord region (Vc/C 1-2 ) was analyzed with gene arrays after treating rats with physiological doses of 17 β-estradiol (Puri et al, 2011). A subunit of the GABA A receptor, Gabrα6, was affected by 17 β-estradiol in the TG and Vc-C 1 (Puri et al, 2011). In addition, a later study found Gabrα6 positive neurons located in the TG projected to the temporomandibular joint (TMJ) (Puri et al, 2012).…”
Section: Introductionmentioning
confidence: 99%